Profil enzimologi hepar sapi bali (Bos sondaicus) di Pulau Timor - Martina O. Yohanes; Antin Y.N. Widi; Putri Pandarangga (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Blood chemistry profile is one of the parameters that can be used to aid the diagnosis of a disease that involves damage in organs e.g. liver. Liver damage can be diagnosed by the examination of elevated liver enzymes such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The range of normal values of ALT and AST is required as a reference in the diagnosis, especially in bali cattle. East Timor is one of the distribution areas of bali cattle with a total population of 504974 cattles. This number has decreased from the previous year because of the many factors such as health problems. This study aimed to determine the range of the value of ALT and AST bali cattle in the district of Kupang and TTS based on gender and age ranges. The data obtained can be used as the reference value in the bali cattle in the district of Kupang and TTS. Samples were taken from 80 bali cattles (22 females, 18 males, 20 with age 2 years old or more, and 20 with age 2 years old or less) that were clinically healthy. Blood samples were taken through the jugular vein and assayed using MicroLab 300. The results were obtained using descriptive analysis SPSS 16. The results showed that the level of ALT and AST in bali cattles on East Timor have an average 36.45 (U/L) (±11.87) and 85.51 (U/L) (±39.11). Based on the results, the value of ALT and AST level of bali cattle in East Timor in May-June 2016 were not influenced by gender and age. The results provide a reference value normal blood clinical chemistry bali cattle on East Timor.